Transfers from College to One Ontario University: A Four-Year Outcome Study - Stewart, Jo; Martinello, Felice (Canadian Journal of Higher Education, 2015)
In this follow-up study, college students who transferred to one Ontario university in 2008–2009 were compared to non-transfer students using several different measures of academic success at university. When compared to non-transfer students, college transfer students earned fewer credits each year, had lower GPAs, and were less able to earn credits from course attempts. The differences were small for students’ first and second years but larger in years three and four. Despite the lower GPA, college transfer students were not more likely than non-transfer students to be eligible for academic suspension. College transfer students also attempted fewer courses and were much less likely to persist to Year 4. By spring 2012 (after four years of university), the college transfer students were more likely than non-transfer students to have graduated, but their degree of choice was a 15-credit three-year degree (as opposed to a 20-credit four-year honours or non-honours degree). Policy implications are discussed.